Investigations of a journalistic blind spot - Figenschou Tine Ustad; Eide Elisabeth; Einervoll Nilsen Ruth (Nordicom Review)
Recent studies argue that the contemporary working class has largely disappeared from the news media. Another strand of literature demonstrates that the traditional labour beat has lost newsroom prestige due to changes in the established news media and crisis in the labour movement. Analysing how traditional working-class sectors are covered in mainstream newspapers and trade union magazines over time, we conduct a systematic, quantitative content analysis of 18 months of coverage from 1996–2017. We find a steady decline in media coverage throughout the period, indicating that the labour beat as an established specialisation is disappearing. Studying topical emphasis and source practices demonstrates marked differences between the newspapers and the trade union magazines: The mainstream newspapers are elite- and conflict-oriented (although not hostile in their coverage), while the trade union magazines largely reflect power structures and the interests of the labour movement. In the discussion, the main findings from the content analysis are explained by practitioners, to contextualise and provide insider perspectives on the findings.